Pembelajaran Tasawuf di Pondok Pesantren Salafiyah Bandar Kidul Kota Kediri - Kadi Kadi; Hidayatul Khoiriyah (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
The term Sufism is indeed familiar among Muslim scholars, which is known as a way of approaching the human self with God, which researchers feel is necessary for all humans to know. This study aims to determine and analyze Sufism Learning, Sufism Learning Methods and Sufism Learning Approaches. In this research, the writer uses field research which is ethnomethodology-qualitative. The results of the research carried out, namely: Materials or Sufism Learning Curriculum at the Salafiyah Islamic Boarding School Bandar Kidul, Kediri City using classical books (yellow books) from the Sufism perspective including: 'Aqi>datul 'Layers and also using the Mu'taqod Question Answer method, Jawa>hirul Kala>miyyah, Tija>nud Duroriy, Kifa>yatul 'Awam and Husunul Hamidiyah, Ihya' 'Ulu>middin and the book of Al-Hikam, Sufism Learning Methods at Islamic Boarding Schools Salafiyah Bandar Kidul in Kediri City by using the Ngaji Bandongan, Tirakat, Majlis Ta'lim and Lecture Methods as well as the Sufism Learning Approach at the Salafiyah Islamic Boarding School in Bandar Kidul, Kediri, by using the Takhalli, Tahalli and Tajalli approaches